OPTIMATION PROCESS AND KINETICS OF EPOXIDATION OF Jatropha curcas L. OIL BY HYDROGEN PEROXIDE - Ratri Ariatmi N, Djumali Mangunwidjaja, Ani Suryani, Machfud dan Sudradjat (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTJatropha curcas oil (JCO) characterized with an iodine value of 90.4 g/100 g, 47.93% oleic acid and 34.42% linoleic acid, was epoxidised in situ with hydrogen peroxide as oxygen donor and acetic acid glacial as active oxygen carrier in the presence of inorganic acid catalyst (H2SO4). The results showed that H2SO4 was found effective in terms of conversion to oxirane. The effects of various factors (variables), such as temperature, hydrogen peroxide-to acetic acid mole ratio, and catalyst volume ratio, on epoxidation rate as well as on the oxirane ring stability and iodine value of curcas oil epoxidised (ECO) were studied. The effects of these variables on the conversion to epoxidised oil were also studied. The constant rate of reaction and activation energy for epoxidation of curcas Oil (CO) was found to be an order of 10_6 l mol_1 det_1 and 6.92 kcal mol_1K-1. General conclusion showed that it was possible to make epoxides using natural renewable resources such as CO. Keywords : In situ epoxidation; kinetics ;jatropha curcas oil; hydrogen peroxide; peracetic acid.